Литовсько-католицькі князі в Сіверській землі: 1401–1452 рр. - Келембет, С. (Сiверянський лiтопис, 2019)
За весь період входження Сіверської землі до складу Великого князівства Литовського удільні князівства в її межах надавалися лише двом представникам династії
Ґедиміновичів, які сповідували католицизм. Швитриґайло Ольґердович у різні періоди
свого життя був князем Брянським (1406–1408), Чернігівським (1420–1430) і Гомельським (1447/48–1452). Його двоюрідний брат, Жиґимонт Кейстутович, володів
Гомелем (1398/1401–1432), Стародубом і Брянськом (1408/09–1432). Михайлушко
Жиґимонтович лише ненадовго, за допомогою татар, зміг захопити Стародуб та
кілька інших міст (1449). У даній роботі досліджуються питання хронології правління
зазначених князів на Сіверщині, складу їхніх володінь, а також інші факти біографій
Швитриґайла, Жиґимонта й Михайлушка, пов’язані із «сіверськими» періодами їхнього життя. The article examines the issue of the Lithuanian princes of the Catholic religion, members
of the Gedyminovych dynasty, who were the rulers of the specific principalities within the Siver
land. In fact, we are talking only about two princes – Shvitrigailo-Boleslaw Olgerdovych,
brother of King Wladyslaw II-Yagailo of Poland, and Sigismund Keistutovych, a brother of
Grand Duke of Lithuania Vitovt-Alexander. Before them, all the princes of Lithuanian origin,
who received possession in the Siver land, were necessarily of Orthodox religion. Obviously,
the fact of the «imposition» by Vilnius of the Catholic princes to the Russian-Orthodox region
was directly connected with the strengthening of the power of Vitovt, during which the Grand
Duchy of Lithuania reached its highest power.
In the biography of Shvitrigailo Olgerdovych there are four periods that are characterized
by the presence of one or other possessions in Siver land. 1) From 1406 to 1408 under the rule
of Shvitrigaila were Bryansk and Starodub, that is, the northern part of the Siver land. 2) In
1420, a specific principality was created for Shvitrigailo in another, southern part of the Siver
land, which included Chernigov, Novgorod-Siversky and Trubchevsk. This princedom existed
until 1430, when Shvitrigailo himself occupied the grand prince throne in Vilnius. 3) During
the civil war in the Grand Duchy of Lithuania in 1432-1438, when Shvitrigailo was in fact
only the «Grand Duke of Russia» (without Lithuania), his power was recognized by the whole
of Siver land (with a short break). 4) During the reign of Shvitrigailo in Volhynia, in 1447
(1448?), he received Gomel in the northwestern part of the Siver land, which he obviously
owned until his death in 1452.
Sigismund Keistutovych between 1398 and 1401 received Gomel. Then, obviously, soon
after 1408, the former possessions of Shvitrigailo – Starodub and Bryansk were transferred
to him. The Starodub Principality existed until 1432, when Sigismund himself occupied the
grand duke’s throne in Vilnius. In 1449, the son of Sigismund, Mikhailushko, with the help
of the Tatars captured several Siver cities, including Starodub and Bryansk; however, he was
soon expelled from there by King Casimir Yagellon.